2016
DOI: 10.1902/jop.2015.150549
|View full text |Cite
|
Sign up to set email alerts
|

Implant Abutment Cleaning by Plasma of Argon: 5‐Year Follow‐Up of a Randomized Controlled Trial

Abstract: Plasma of argon could be used to disinfect implant abutments before insertion to minimize future peri-implant bone resorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 31 publications
1
46
0
Order By: Relevance
“…In vitro studies have demonstrated that plasma of argon treatment can activate the surfaces at the atomic and molecular levels, preserving the integrity of the titanium surface (Canullo et al 2016b). This activation enhances the activity of bone-forming cells at the tissue-implant interface (Canullo et al 2016a). The results of the present in vivo study confirm the outcomes of the already published interim study (Canullo et al 2014a,b), where 18 patients were treated with dental implants and 18 abutments were connected at the second surgery.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In vitro studies have demonstrated that plasma of argon treatment can activate the surfaces at the atomic and molecular levels, preserving the integrity of the titanium surface (Canullo et al 2016b). This activation enhances the activity of bone-forming cells at the tissue-implant interface (Canullo et al 2016a). The results of the present in vivo study confirm the outcomes of the already published interim study (Canullo et al 2014a,b), where 18 patients were treated with dental implants and 18 abutments were connected at the second surgery.…”
Section: Discussionsupporting
confidence: 90%
“…; Canullo et al. ). In vitro studies have demonstrated that plasma of argon treatment can activate the surfaces at the atomic and molecular levels, preserving the integrity of the titanium surface (Canullo et al.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations